Analisis Pemikiran Ibnu Hazm Tentang Kesaksian Wanita dalam Pidana Zina - Mukhsin Nyak Umar (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2012)
Testimony is valid evidence to obtain legal certainty. Of proof in criminal adultery with a request for information made four male witnesses as represented in the texts of the Koran. Ibnu Hazm practice texts generality arba'ati syuhada include men and women and reject hadis munqathi' basis for justification of testimony limited to the male gender only. This argument is the basis for Ibn Hazm allowing women to testify in criminal adultery while guided by the principle of equality of men and women. In addition, Ibnu Hazm also rejected the psychological condition of women as a reason for refusing the testimony of women in certain fields. This condition can be anticipated by the number of witnesses more women than men because the Qur'an clearly define terms that are fair witness is owned by men and women